Case report: Uterine leiomyoma with fumarate hydratase deficiency - Diana Bužinskienė; Diana Bužinskienė; Dominyka Grinciūtė; Mindaugas Šilkūnas; Mindaugas Šilkūnas; Evelina Šidlovska (Frontiers in Medicine, 2024)
Hereditary leiomyomatosis and renal cell cancer syndrome is a rare autosomal dominant disease caused by mutations in the fumarate hydratase gene. The syndrome is characterized by skin leiomyomatosis, uterine leiomyomatosis, and renal cell carcinoma. Herein, we report a case of fumarate hydratase deficient leiomyoma. The patient was a young female presenting with large uterine leiomyoma and multiple kidney angiomyolipomas. The report presents the chosen treatment and the challenges of differential diagnosis.